Benchmarking that Matters: Rethinking Benchmarking in Continuous Optimisation for Practical Impact - Kononova, Anna V.; van Stein, Niki; Mersmann, Olaf; Bäck, Thomas; Bartz-Beielstein, Thomas; Glasmachers, Tobias; Hellwig, Michael; Krey, Sebastian; Kudela, Jakub; Naujoks, Boris; Papenmeier, Leonard; Raponi, Elena; et al. (Applications of Evolutionary Computation - 29th European Conference, EvoApplications 2026, Held as Part of EvoStar 2026, Toulouse, France, April 8-10, 2026, Proceedings, Part II)

LLM Driven Design of Continuous Optimization Problems with Controllable High-Level Properties - Skvorc, Urban; van Stein, Niki; Seiler, Moritz; Grimme, Britta; Bäck, Thomas; Trautmann, Heike (Applications of Evolutionary Computation - 29th European Conference, EvoApplications 2026, Held as Part of EvoStar 2026, Toulouse, France, April 8-10, 2026, Proceedings, Part II)

Investigating the representation of backchannels and fillers in fine-tuned language models - Wang, Yu; Lao, Leyi; Huang, Langchu; Skantze, Gabriel; Xu, Yang; Buschmeier, Hendrik (Proceedings of the 64th Annual Meeting of the Association for Computational Linguistics)
Backchannels and fillers are important linguistic expressions in dialogue, but often treated as "noise" to be bypassed in modern transformer-based language models. Our work studies the representation of them in language models using three fine-tuning strategies. The models are trained on three dialogue corpora in English and Japanese, where backchannels and fillers are preserved and annotated, to investigate how fine-tuning can help LMs learn their representations. We first apply clustering analysis to the learnt representation of backchannels and fillers, and have found increased silhouette scores in representations from fine-tuned models, which suggests that fine-tuning enables LMs to distinguish the nuanced semantic variation in different backchannel and filler use. We also use natural language generation (NLG) metrics and qualitative analysis to confirm that the utterances generated by fine-tuned language models resemble human-produced utterances more closely. Our findings suggest the potentials of transforming general LMs into conversational LMs that are more capable of producing human-like languages adequately.

Die 'gute' Mutter - Eine diskursanalytische Untersuchung von Mutterschaft in Sozialen Medien - Menzel, Tessa-Marie
In diesem Open-Access-Buch untersucht Tessa-Marie Menzel das Ideal und die diskursive Hervorbringung der 'guten' Mutter in Sozialen Medien. Im Zentrum steht die App Instagram als digitale Öffentlichkeit, in der sogenannte Momfluencerinnen Mutterschaft öffentlich inszenieren und normativ rahmen. Vor dem Hintergrund widersprüchlicher gesellschaftlicher Erwartungen zwischen intensiver Fürsorge und weiblicher Selbstverwirklichung wird mit Hilfe einer Diskursanalyse untersucht, welches Bild der 'guten' Mutter (re-)produziert und legitimiert wird. Anhand von sechs normativen Figuren ‚guter‘ Mutterschaft zeigen die Ergebnisse, dass konkurrierende Anforderungen zu einem scheinbar mühelosen Ideal verschmelzen, bei dem Stress zum Statussymbol wird und Mutterschaft an soziale und ökonomische Privilegien gebunden ist.
Keywords: Mutterschaft; Instagram; Diskursanalyse; Sozialpädagogik; Erziehungswissenschaft

How hard is it to verify a classical shadow? - Karaiskos, Georgios; Rudolph, Dorian; Meyer, Johannes Jakob; Eisert, Jens; Gharibian, Sevag (International Colloquium on Automata, Languages, and Programming (ICALP))
Classical shadows are succinct classical representations of quantum states which allow one to encode a set of properties P of a quantum state rho, while only requiring measurements on logarithmically many copies of rho in the size of P. In this work, we initiate the study of verification of classical shadows, denoted classical shadow validity (CSV), from the perspective of computational complexity, which asks: Given a classical shadow S, how hard is it to verify that S predicts the measurement statistics of a quantum state? We show that even for the elegantly simple classical shadow protocol of [Huang, Kueng, Preskill, Nature Physics 2020] utilizing local Clifford measurements, CSV is QMA-complete. This hardness continues to hold for the high-dimensional extension of said protocol due to [Mao, Yi, and Zhu, PRL 2025]. Among other results, we also show that CSV for exponentially many observables is complete for a quantum generalization of the second level of the polynomial hierarchy, yielding the first natural complete problem for such a class.

Boundary values of diffeomorphisms of simple polytopes, and controllability - Glöckner, Helge; Grong, Erlend; Schmeding, Alexander (Differential Geometry and its Applications)

“It’s the 21st century, but this is still a boy’s club” - Gender, money and power in Inventing Anna - Intveen, Julie (MEIN FACH Englisch Sek II)

Emotionale Aktivierung - Großkrüger, Denise; Roberts, Claire; Schmidt, Rebekka (KUNST+UNTERRICHT (Beilage: IM FOKUS))

Sozial-konstruktivistische Aktivierung - Großkrüger, Denise (KUNST+UNTERRICHT (Beilage: IM FOKUS))

Identifying the periodicity of information in natural language - Ou, Yulin; Wang, Yu; Xu, Yang; Buschmeier, Hendrik (Proceedings of the 64th Annual Meeting of the Association for Computational Linguistics)
Recent theoretical advancement of information density in natural language has brought the following question on desk: To what degree does natural language exhibit periodicity pattern in its encoded information? We address this question by introducing a new method called AutoPeriod of Surprisal (APS). APS adopts a canonical periodicity detection algorithm and is able to identify any significant periods that exist in the surprisal sequence of a single document. By applying the algorithm to a set of corpora, we have obtained the following interesting results: Firstly, a considerable proportion of human language demonstrates a strong pattern of periodicity in information; Secondly, new periods that are outside the distributions of typical structural units in text (e.g., sentence boundaries, elementary discourse units, etc.) are found and further confirmed via harmonic regression modeling. We conclude that the periodicity of information in language is a joint outcome from both structured factors and other driving factors that take effect at longer distances. The advantages of our periodicity detection method and its potentials in LLM-generation detection are further discussed.

When “yeah” means “not quite”: Multimodal detection of backchannels expressing incomplete understanding - Türk, Olcay; Lazarov, Stefan Teodorov; Wang, Yu; Grimminger, Angela; Buschmeier, Hendrik; Wagner, Petra (Proceedings of INTERSPEECH 2026)
Multimodal backchannels are fundamental to conversational grounding and understanding. However, backchannels do not always transparently reflect the interlocutor's actual cognitive state. “Incongruent backchannels”, where the observable feedback implies understanding although there is no genuine understanding, are a potential source of ambiguity in any interaction. Using acoustic, head movement, and discourse-related data from 45 naturalistic dyadic interactions, we investigate whether incongruent and congruent backchannels show systematically different properties using a classification task. Results show that these backchannels are indeed separable based on multimodal features. Incongruent backchannels are typically characterised by more neutral head movement configurations and lower acoustic dynamism, while discursive cues strongly influence the classification. Overall, the findings suggest a relatively reduced effort in the signalling of incongruent backchannels.

Equipping street-level bureaucrats with green skills for sustainable public policy change - Kesternich, Martin; Kiepe, Karina; Reimsbach, Daniel; Trang, Simon Thanh-Nam; Yang, Philip (npj Climate Action)
Abstract The shift to a low-carbon economy requires developing green skills across sectors. This paper builds on a recent Perspective 1 article examining how institutional regimes shape green skill formation. Drawing on the microfoundations of management research, we propose a micro-level perspective of public sector green skill formation, thereby emphasizing the role of street-level bureaucrats serving as public servants who directly engage with citizens in implementing public policies and outline a research agenda.

Lehrkräftebildung kann jeder? Berufspädagogisch orientierte Profilierung des Lehramts an berfusbildenden Schulen - Kremer, H.-Hugo; Jenert, Tobias; Sloane, Peter F. E.; Beutner, Marc; Kiepe, Karina (Professionalität und Professionalisierung des beruflichen Bildungspersonals. Festschrift für Ulrike Weyland)

Navigating Transfer Pricing Complexity: Standardization, Cooperation, Transparency - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren (eJournal of Tax Research)
This study examines the drivers of perceived corporate transfer pricing complexity. Our analysis is based on survey data from multinational firms in the manufacturing sector. We identify three key strategies expected to reduce transfer pricing complexity and associated compliance costs while enhancing tax compliance: standardising transfer pricing documentation, strengthening cooperation between tax authorities, and increasing transparency through expanded information exchange among tax authorities and between tax authorities and firms. The findings provide evidence-based insights for international tax policy aimed at reducing transfer pricing complexity and associated administrative burdens for both firms and tax administrations.

Leadership practices in implementing early mathematics education as a curriculum innovation into vocational training of early childhood education - Bruns, Julia; Gasteiger, Hedwig; Hallemann, Svea; Schopferer, Theresa (Research in Mathematics Education)

Forschendes Lernen im Praxissemester des Faches Englisch - Niesen, Heike; Rumlich, Dominik (Handlungsorientierung in der Ausbildung von Lehrkräften und pädagogischen Fachkräften)

Die "jüngere Queerfeminist*in spricht" antizionistisch. Queerer Antifeminismus und der Hass auf Israel - Vukadinovic, Vojin Sasa (Akademischer Antisemitismus. Wie Forschung und Lehre Judenhass begründen und verbreiten)

Wider die Tristesse von Alltag und Innerlichkeit. Vorspiel einer Malerei gebrochener Vertrautheit: Lewandowski, Gil, Pieniak - Vukadinovic, Vojin Sasa (Jahrbuch Sexualitäten 2026)

Der Traum ihrer Verkommenheit. Anmerkungen zu Christa Reinigs Frühwerk - Vukadinovic, Vojin Sasa („bin weiblich, bin männlich, doppelt“. Queere DDR-Literatur)

Mass Functions and Asymptotic Behavior of Caloric Functions on Affine Buildings - Papageorgiou, Efthymia; Trojan, Bartosz (Mathematische Annalen)